Black beauty Level 2 - Sewell, Anna; Davage, John; Hopkins, Andy; Potter, Jocelyn (London Pearson Education Limited, 2008)
This book is about the life of a beautiful horse as a colt, adult, and retired animal and addresses issues horses had to deal with in regards to being used to pull carriages for money making and about the fair and kind treatment of animals used by people.
.
Keywords: Tham khảo